Arrhythmic risk stratification in non-ischaemic dilated cardiomyopathy beyond ejection fraction. Issue 9 (21st January 2020) - Cannatà, Antonio; De Angelis, Giulia; Boscutti, Andrea; Normand, Camilla; Artico, Jessica; Gentile, Piero; Zecchin, Massimo; Heymans, Stephane; Merlo, Marco; Sinagra, Gianfranco
Abstract : Sudden cardiac death and arrhythmia-related events in patients with non-ischaemic dilated cardiomyopathy (NICM) have been significantly reduced over the last couple of decades as a result of evidence-based pharmacological and non-pharmacological therapeutic strategies. Nevertheless, the arrhythmic stratification in patients with NICM remains extremely challenging, and the simple indication based on left ventricular ejection fraction appears to be insufficient. Therefore, clinicians need to go beyond the current criteria for implantable cardioverter-defibrillator implantation in the direction of a multiparametric evaluation of arrhythmic risk. Several parameters for arrhythmic risk stratification, ranging from electrocardiographic, echocardiographic, imaging-derived and genetic markers, are crucial for proper arrhythmic risk stratification and a multiparametric evaluation of risk in patients with NICM. In particular, integration of cardiac magnetic resonance parameters (mostly late gadolinium enhancement) and specific genetic information (ie, presence of LMNA, PLN, FLNC mutations) appears fundamental for proper implementation of the current arrhythmic risk stratification. Finally, a novel approach focused on both arrhythmic risk and prediction of left ventricular reverse remodelling during follow-up might be useful for effective multiparametric and dynamic arrhythmic risk stratification in NICM. In the future, a complete and integrated evaluation might be mandatory to implement arrhythmic risk prediction in patients with NICM and to discriminate the competing risk between heart failure-related events and life-threatening arrhythmias.